Adherence to the therapeutic guidelines recommendations among the people with type 2 diabetes mellitus and obesity, frailty, or recent diagnosis, attended in primary health care centers in Spain: A cross-sectional study - Vlacho, Bogdan; Mata-Cases, Manel; Fernandez-Camins, Berta; Romera Liébana, Laura; Barrot-de la Puente, Joan; Franch-Nadal, Josep (Frontiers in Medicine, 2023)
This study aimed to evaluate the degree of adherence to the recommendations of the Clinical Practice Guidelines (CPG) among obese, frail, or recently diagnosed type 2 diabetes mellitus (T2DM) participants in primary care centers in Spain. We perform a cross-sectional study on a national level in two phases. In the first phase, study participants were recruited, and their clinical data were collected. In the second phase, data related to the participating physicians were collected. In total, 882 participants from 240 physicians were analyzed. According to the study questionnaire, the majority of participants from all three clinical groups had adequate adherence to the CPG. This percentage was highest among the recently diagnosed T2DM (91.6%) and lowest percent of frail T2DM persons (74.7%). The inadequate adherence to the guidelines was observed mainly among the obese and frail participants with T2DM from medical doctors with low CPG knowledge (3.4% and 3.5%, respectively). Regarding the patient's characteristics and degree of adherence to the guidelines, the participants with inadequate adherence were generally older, with higher BMI, poorer HbA1c control, and fewer visits with primary care physicians. Most (57%) of the primary care physicians had moderate CPG knowledge. In our multivariable logistic model, we did not observe statistically significant odds ratios for different characteristics related to the physicians/consultation and low CPG knowledge. In conclusion, the results of our cross-sectional study observe adequate adherence to the clinical guidelines by the primary care physicians for the majority of the participants with obesity, frailty, or newly diagnosed with T2DM.